Carpal tunnel syndrome a study on the prevalence and risk factors among manila dentists - Saculo, Jennifer F.; Lara, Teresita (Adviser).
The research was performed to determine the prevalence of the symptoms of Carpal Tunnel Syndrome among Manila Dentists. Moreover, it also aimed to determine possible risk factors that might be associated to the occurrence of such symptoms. Questionnaires were administered the 44 subject dentists from various districts of Manila. Information gathered were tabulated and computed to determine the percentages, means and frequencies of different categorical questions. The results showed that there were 16 dentists found to be positive to the standard tests given. One dentist in particular was already diagnosed to have the condition. In addition to that, several risk factors were analyzed and correlated to the possible occurrence of the symptoms of CTS. As conclusion, tingling sensations and numbness were noted to be the most common symptoms experienced by dentists that may be related to CTS.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.